The Influence of Leadership Quality on Lecturer Performance through Communication Patterns and Human Resource Control Management - Muhammad, Ybnu T; Ansar; Farida, Umi; Tamsah, Hasmin (Journal of Indonesian Scholars for Social Research, 2023)
This study aims to elaborate and analyze the influence of leadership quality on lecturer performance through communication patterns and human resource control management and its impact on internal quality assurance at universities. This research is quantitative with an exploratory approach, which was conducted at Tomkaka University Mamuju, West Sulawesi Province. The population of this study were all lecturers from 7 faculties, namely 152 people, with saturated sampling technique so that all lecturers were research samples. The research instrument used interviews and questionnaires as data collection tools. For data analysis, SEM-PLS is used to test the direct and indirect effects of the conceptual model created. This study shows the findings that 1) leadership quality improves communication patterns; 2) leadership quality improves human resource control management; 3) leadership quality improves lecturer performance; 4) communication patterns improve lecturer performance. This facet examines how strategic management of human resources contributes to optimizing lecturer performance. It includes aspects like recruitment, training, performance appraisal, and feedback mechanisms. The theme suggests that adept management of these elements by leaders can lead to a more engaged, motivated, and competent faculty. The theme emphasizes the importance of effective communication within academic institutions. It explores how clear, transparent, and consistent communication from leaders can enhance understanding, build trust, and foster a collaborative environment, thereby improving lecturer performance.